Navigating physical activity engagement following a diagnosis of cancer: A qualitative exploration. (7th December 2016) - Cummins, C.; Kayes, N.M.; Reeve, J.; Smith, G.; MacLeod, R.; McPherson, K.M.
Abstract : This qualitative descriptive study explored cancer survivors' experiences of barriers and facilitators to undertaking physical activity to inform how services and professionals might offer better support. Purposive and theoretical sampling was used to recruit 25 people who were up to 5 years post‐cancer diagnosis. Participants took part in face to face, semi‐structured interviews, and transcripts were analysed using thematic analysis. The analysis identified five interrelated themes which represented cancer survivors' views: 1) You're on your own –a sense of abandonment post‐treatment, and lack of sufficient and tailored information; 2) Dis‐ease –disruption to self and identity, and a heightened awareness of physical self and fragility; 3) Becoming acclimatised –physical activity in the face of treatment‐related side effects and residual impairment; 4) Importance of others –encouragement and support from health professionals, family and friends, and cancer‐specific exercise groups; 5) Meanings people ascribed to physical activity —these were central and could help or hinder engagement. Our findings suggest being able to live well and re‐engage in meaningful activities following a diagnosis of cancer is both complex and challenging. There appear to be gaps in current service provision in supporting the broader health and well‐being of cancer survivors.